2006
DOI: 10.1136/bmj.38725.728472.be
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors for meningococcal disease in adolescents: matched cohort study

Abstract: Objective To examine biological and social risk factors for meningococcal disease in adolescents. Design Prospective, population based, matched cohort study with controls matched for age and sex in 1:1 matching. Controls were sought from the general practitioner. Setting Six contiguous regions of England, which represent some 65% of the country's population. Participants 15-19 year olds with meningococcal disease recruited at hospital admission in six regions (representing 65% of the population of England) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
1
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(77 citation statements)
references
References 45 publications
(59 reference statements)
3
66
1
6
Order By: Relevance
“…Of those, eight (67%) reported lower infection rates or lower viral load in those who were more R/S, and no study found greater infection or higher viral load. Of the 10 best studies, seven (70%) found significant inverse associations between R/S and infection or viral load [216][217][218][219][220][221][222]. There is also a wealth of research linking R/S involvement or interventions to better immune function (14 of 27 studies) [223] and endocrine function (lower cortisol levels in 19 of 29 studies) [224], both of which are known to influence both infection risk and speed of wound healing.…”
Section: Cardiac Surgery Outcomesmentioning
confidence: 99%
“…Of those, eight (67%) reported lower infection rates or lower viral load in those who were more R/S, and no study found greater infection or higher viral load. Of the 10 best studies, seven (70%) found significant inverse associations between R/S and infection or viral load [216][217][218][219][220][221][222]. There is also a wealth of research linking R/S involvement or interventions to better immune function (14 of 27 studies) [223] and endocrine function (lower cortisol levels in 19 of 29 studies) [224], both of which are known to influence both infection risk and speed of wound healing.…”
Section: Cardiac Surgery Outcomesmentioning
confidence: 99%
“…Tully et al (2006) have reported that adolescent students are at increased risk of meningococcal disease due to frequent intimate oral contact with multiple partners. The increased transmission of throat pathogens in this social group doubtless accounts for our finding of co-infection of F. necrophorum with EBV and b-haemolytic streptococci and may also explain the increased likelihood of asymptomatic carriage of F. necrophorum in this social group compared with the healthy non-student adults we have studied previously (Aliyu et al, 2004); 29 of the 411 students (7.1 %) were asymptomatic carriers compared with 0 of 100 (P50.01) in the previously studied healthy non-student adults.…”
mentioning
confidence: 99%
“…Also, the generally graver clinical picture of invasive disease caused by this clone (14,30,51) further delineates its epidemiologic distinctiveness. Another noteworthy feature of ET-15 meningococci is their predilection to strike teenagers (e.g., 59% of the ET-15 cases between 2002 and 2005 in Germany were over 10 years old), who represent an age group for which different activities and events have been shown to increase the risk of acquiring IMD further than the risk in childhood (45). For the monitoring of circulating meningococcal strains, we employ a finetyping routine encompassing the determination of the serogroup and sequence-based typing of the variable regions of the outer membrane proteins PorA and FetA.…”
Section: Resultsmentioning
confidence: 99%
“…45,2007 IS1301 RFLP OF Further intragenic insertions were found in ORFs homologous to the adhesin MafB (36) and to the T-cell-and B-cellstimulating Neisseria-specific antigen TspB (GenBank accession no. AJ010115).…”
Section: Discussionmentioning
confidence: 99%